The state of Islam : culture and Cold War politics in Pakistan - Toor, Saadia, 1971- (London : Pluto Press ; New York : Distributed by Palgrave Macmillan, 2011)
"The state of Islam tells the story of Pakistan through the lens of the Cold War, and more recently, the War on Terror, to shed light on the domestic and international processes behind the rise of militant Islam. Unlike existing scholarship on nationalism, Islam and the state of Pakistan, which tends to privilege events in a narrowly-defined ''political' realm, Saadia Toor highlights the significance of cultural politics in Pakistan from its origins to the contemporary period. This extra dimension allows Too to explain how the struggle between Marxists and liberal nationalists was influenced and eventually engulfed by the agenda of the religious right." -- [P] 4 of cover.
Introduction -- Consolidating the Nation-State: East Bengal and the politics of national culture -- Post-partition literary politics: The Progressive versus the nationalists -- Ayub Khan's decade of development and its cultural vicissitudes -- From Bhutto's authoritarian populism to Zia's military theocracy -- The long shadow of Zia: women, minorities and the nation-state -- Epilogue: The neoliberal security state.
Includes bibliographic references (p. 234-244) and index.
Keywords: Islam and politics -- Pakistan; Islam -- Pakistan; Cold War; Pakistan -- Politics and government; Pakistan -- History -- 1947-